Optimization of Illumina® Nextera™ XT library preparation for whole mitochondrial genome sequencingand confirmatory Sanger sequencing - Nejira Handžić; Dino Pećar; Selma Durgut; Naida Mulahuseinović; Ivana Čeko; Adna Ašić; Mirza Izmirlija; Sabina Šegalo; Lana Salihefendić; Rijad Konjhodžić (Medicinski glasnik, 2025)
Aim: Due to increasing use of mitochondrial DNA (mtDNA) sequencing in both forensic practice and clinical disease research, this study explores the optimization of the next-generation sequencing (NGS) method for whole mitochondrial genome analysis on the Illumina MiSeq platform. Methods: Initial attempts using pre-made commercial primers were unsuccessful, leading to the design of novel custom-designed primers in our laboratory and optimization of sequencing chemistry and protocols. A comprehensive protocol was developed, involving long-range amplification, enzymatic fragmentation, and the use of IDT® for Illumina DNA/RNA UD Indexes and MiSeq Reagent Nano Kit v2 (300 cycles), whereby DNA extraction, quantification, and library preparation were all performed according to optimized protocols. Results: Successful amplification was confirmed using gel electrophoresis and Agilent Bioanalyzer, with optimized conditions yielding clear, specific amplicons 9.8 and 8.5 kb in length. Sequencing results demonstrated high-quality reads with an average coverage depth of 742x and a GC content of 43-45%. The study highlights the efficiency of custom primers and individual library normalization for reliable mtDNA sequencing. Conclusion: These findings advance the application of NGS in forensic and clinical settings by enhancing the detection of rare mutations and mitochondrial heteroplasmy, paving the way for routine mtDNA analysis using NGS technology.
Keywords: mitochondrial genome; mutations; next-generation sequencing